Churches as firms: An exploration of regulatory similarities. (19th February 2018) - Patrikios, Stratos; De Francesco, Fabrizio
Abstract: Regulatory states manage religious activity within their jurisdiction in the same way they manage economic activity, in an alignment pattern that reflects institutionally embedded processes. Relying on regulatory institutional options to trace consistencies in the way a regime manages economic and religious activity, the article develops and tests theoretical accounts of the presence and content—in terms of comparative variation—of this alignment. The empirical setting, primarily OECD countries in recent decades, allows us to reverse a conventional causal view and treat religious regulation as causally embedded in the logic and practice of economic regulation. If reliance on regulation as a means of social control is bound by the same processes across domains, this may even suggest the existence of national cross-sectoral models of coordinating competition. The study elaborates a broad conceptualization of regulatory governance with potentially wide applicability.